2017
DOI: 10.1145/3072959.3126796
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of intrinsic and extrinsic geometry

Abstract: We propose a novel way to capture and characterize distortion between pairs of shapes by extending the recently proposed framework of shape differences built on functional maps. We modify the original definition of shape differences slightly and prove that, after this change, the discrete metric is fully encoded in two shape difference operators and can be recovered by solving two linear systems of equations. Then, we introduce an extension of the shape difference operators using offset surfaces to capture ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 12 publications
0
41
0
Order By: Relevance
“…To learn a metric from a mesh, we use its spatial rather than spectral raw features, as the former capture both intrinsic and extrinsic geometry for shape analysis [56]. Specifically, we use the spherical harmonic (SH) descriptors of [47], which are derived from a raw distance field and have a theoretical guarantee of minimal information loss.…”
Section: Implementation Detailsmentioning
confidence: 99%
“…To learn a metric from a mesh, we use its spatial rather than spectral raw features, as the former capture both intrinsic and extrinsic geometry for shape analysis [56]. Specifically, we use the spherical harmonic (SH) descriptors of [47], which are derived from a raw distance field and have a theoretical guarantee of minimal information loss.…”
Section: Implementation Detailsmentioning
confidence: 99%
“…These methods similarly require input for correspondences. Recent work [Corman et al 2017;Rustamov et al 2013] develops effective approaches to measuring shape differences, which are used for embedding shape collections. Given a shape in the first collection, these methods can be used to find a similar shape in the second collection without known correspondence.…”
Section: Mesh Deformationmentioning
confidence: 99%
“…Boscaini et al [BEKB15] showed how to reconstruct shapes from these shape difference operators, enabling shape analogy synthesis and style transfer. While the original shape differences operator captures only intrinsic distortion, Cormen et al [CSBC*17] use offset surfaces to capture extrinsic distortion.…”
Section: Related Workmentioning
confidence: 99%